Clinical Characteristics and Angiographic Profile of Acute Coronary Syndrome Patients in a Tertiary Hospital of Bangladesh - Ahmed, Mohsin; Rubaiyat, Khandaker Abu; Saleh, Mohammed Abaye Deen; Chowdhury, Abdul Wadud; Khuda, CM Khudrate E; Ferdous, Kazi Abul Fazal; Hasan, Nahid; Hoque, Abu Taher Mohammad Mahfuzul; Islam, Kazi Nazrul; Amin, Md Gaffar (Bangladesh Heart Journal, 2018)
Aims: Coronary artery disease is a devastating disease precisely because an otherwise healthy person in the prime of life may die or become disabled without warning. The objectives were to study the clinical profile, risk factors prevalence, angiographic distribution and severity of coronary artery stenosis in acute coronary syndrome (ACS) patients admitted in Cardiology Department of Dhaka Medical College Hospital, Dhaka. Materials and Methods: A total of 800 patients of ACS were analyzed for various risk factors, angiographic patterns and severity of coronary artery disease at DMCH, Dhaka, Bangladesh. Results: Mean age of presentation was 51.27±8.80 years. Majority were male 628 (78.5%) and rest were females (21.5%). Most patients had ST elevated myocardial infarction (STEMI) 509 (63.6%) followed by non-STEMI (NSTEMI) 207 (25.9%) and Unstable Angina (UA) 84 (10.5%). Risk factors: smoking was present in 388 (48.5%), hypertension in 289 (36.13%), diabetes in 235 (29.38%), dyslipidaemia in 169 (21.13%) and obesity in 356 (44.5%) patients. Singlevessel disease was present in 30.32% patients, Doublevessel disease was present in 23.23% patients and Triple vessel disease was present in 27.15% patients. Conclusion: STEMI was the most common presentation. ACS occurred earlier in comparison to Western population. Smoking was most prevalent risk factor. Diabetic patients had more multivessel disease. Bangladesh Heart Journal 2018; 33(1) : 10-15